Birds of Prey Biology and conservation in the XXI century (Springer International Publishing, 2018)
This book will provide the state-of-the-art research on topics involved in the ecology and conservation of birds of prey. With chapters authored by the most recognized and prestigious researchers on each of the fields, this book will become an authorized reference volume for raptor biologists and researchers around the world.